Valuation of Urban Green Open Spaces Using the Life Satisfaction Approach - Retno Setiowati; Raldi H. Koestoer (Salehan Institute of Higher Education, 2024)
This study conducts the valuation of the urban Green Open Spaces (GOS) in Jakarta (Indonesia) using the life satisfaction approach (LSA). We integrated the important elements of the LSA, such as housing structure and environmental facilities, into a comprehensive valuation model (using hedonic variables). By explicitly acknowledging the limited application of these methodologies in developing nations, this study endeavors to provide a context-specific understanding of the economic value of GOS in Jakarta. The LSA model, a novel non-market valuation tool, employs community life satisfaction as its primary metric. In this study, we analyzed the satisfaction levels of residents of Jakarta based on a 10-point scale; the responses of a total of 1,592 participants were collected through online questionnaires in 2021 (during the pandemic). We considered various independent variables, including socioeconomic factors, housing attributes, environmental facilities, location amenities, and the presence of GOS. The analysis involved LSA and ordinary least squares (OLS) models in the Statistical Package for the Social Sciences (SPSS). The results indicate that several variables, such as longer residence duration, good employment status, high income “over 20 million Indonesian Rupiah (IDR); approximately USD 1281.56”, and access to more shopping centers, positively influenced the life satisfaction of the residents, which is in line with the studies conducted in western countries. Surprisingly, the economic evaluation of urban GOS portrayed a limited impact on the residents’ life satisfaction, while negative aspects, e.g., the presence of cemeteries around residential areas (19.1%), impacted the residents significantly. Urban parks did not portray statistical significance in influencing the residents’ life satisfaction, despite having a positive impact across all radii of urban regions. Urban forests exhibited a positive impact, mainly within the 100–500-m radius, with a significant impact on resident life satisfaction. Our attempt to assess the values of landscape amenities in Jakarta using LSA marks a pioneering effort in the field of environmental science with respect to community preferences. Consequently, this study contributes significantly to the evolving yet limited literature in this domain. The results differ from those of the Global North research, emphasizing the need for context-specific urban planning strategies. Our study offers valuable insights for urban planners and government entities and can guide GOS development to enhance urban sustainability and community satisfaction. The implications extend to urban centers in Indonesia and other developing countries, emphasizing the importance of optimizing limited urban spaces based on community preferences. Doi: 10.28991/CEJ-2024-010-04-010 Full Text: PDF